Homrit Akarem Post-Collisional Intrusion, Southeastern Desert, Egypt: Petrogenesis of Greisen Formed in a Cupola Structure and Enrichment in Strategic Minerals - Mokhles K. Azer; Adel A. Surour; Hilmy E. Moussa; Ayman E. Maurice; Mabrouk Sami; Moustafa A. Abou El Maaty; Adel I. M. Akarish; Mohamed Th. S. Heikal; Ahmed A. Elnazer; Mustafa A. Elsagheer; Heba S. Mubarak; Amany M. A. Seddik; et al. (Geosciences, 2025)
The greisens discussed in the present study are associated with the Homrit Akarem post-collisional granites, which are exposed near the western edge of the Egyptian Nubian Shield in the Southeastern Desert of Egypt. The Homrit Akarem granites intruded into Neoproterozoic country rocks, with sharp intrusive contacts. The marginal parts of the Homrit Akarem intrusion underwent extensive post-magmatic metasomatism, resulting in the formation of albitized granite and greisens. The Homrit Akarem greisens occur as veins and stockworks, which can be classified into four types: muscovite-rich, cassiterite-rich, topaz-rich, and beryl-rich greisens. Based on petrographic inspection, we identified ore minerals (cassiterite, beryl, topaz, muscovite, Nb-Ta oxides, tourmaline, fluorite, and corundum) in the greisens using electron probe microanalysis. The Homrit Akarem mineralized greisens were formed in a magmatic cupola above A-type magma, where fluid–rock interactions played a significant role in their formation. The accumulation of residual volatile-rich melt and exsolved fluids in the apical part of the magma chamber produced albitized granite, greisens, and quartz veins that intruded into the peripheries of the granitic intrusion and its surrounding country rocks. The variation in the mineralogy of the studied greisens indicates the diverse chemical composition of both the hydrothermal/magmatic fluids and the host granites. The simultaneous decrease in temperature and pressure is considered a crucial factor that controlled mineralization in the apical parts of the magma chamber. The occurrence of cassiterite, beryl, topaz, tourmaline, muscovite, and Nb-Ta oxides in the studied greisens suggests a potential polymetallic deposit of industrial minerals.